Diagnostic Value of Serum Amylase Levels Indicating Computed Tomography–Defined Post–Endoscopic Retrograde Cholangiopancreatography Pancreatitis: A Prospective Multicenter Observational Study. Issue 7 (August 2020) - Inatomi, Osamu; Bamba, Shigeki; Nakai, Yoshitaka; Kusumoto, Kiyonori; Kawakami, Takumi; Suzuki, Takahiro; Suzuki, Azumi; Endoh, Bunji; Ota, Shinichi; Inoue, Akitoshi; Itokawa, Yoshio; Chikugo, Koki; et al.
Abstract : Objective: Post–endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis involves persistent serum amylase levels of 3 times or more the standard upper limit. However, these criteria were mostly based on retrospective studies and not necessarily supported by diagnostic imaging. Our prospective study aimed to investigate cutoff serum amylase levels suggesting post-ERCP pancreatitis using computed tomography as the criterion standard. Methods: We prospectively followed 2078 cases. Computed tomography was performed in patients whose serum amylase levels exceeded the institutional upper limit 12 to 24 hours after ERCP. Two expert radiologists blindly assessed the images and judged the presence or absence of pancreatitis. Correlations between serum amylase levels with pancreatitis were investigated using receiver operating characteristic analysis. Results: Amylase levels increased in 416 (23.2%) of 1789 cases included, and 350 cases were analyzed using computed tomography. Post–endoscopic retrograde cholangiopancreatography pancreatitis was diagnosed in 12.0% (214/1789). The cutoff amylase levels for judging pancreatitis after 12 to 24 hours was 2.75 times higher than the institutional upper limit, with an area under the curve of 0.77. Conclusions: The appropriate cutoff serum amylase level for judging post-ERCP pancreatitis at 12 to 24 hours after ERCP was 2.75 times higher than the institutional upper limit. These results may clarify the definition of post-ERCP pancreatitis.